2010
DOI: 10.1186/1472-6882-10-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses and visit length in complementary and mainstream medicine

Abstract: BackgroundThe demand for complementary medicine (CM) is growing worldwide and so is the supply. So far, there is not much insight in the activities in Dutch CM practices nor in how these activities differ from mainstream general practice. Comparisons on diagnoses and visit length can offer an impression of how Dutch CM practices operate.MethodsThree groups of regularly trained physicians specialized in CM participated in this study: 16 homeopathic physicians, 13 physician acupuncturists and 11 naturopathy phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Every definition notes that CAM therapies are not part of conventional biomedicine, though the exact phrasing differs and some authors note the intrinsic relativism of any such criterion 1,10 . Indeed, the boundary between conventional medicine and CAM is increasingly muddy as medical schools, general practitioners and hospitals worldwide have introduced CAM therapies alongside mainstream biomedical therapy 16,17,18 , and official regulatory bodies acknowledge and licence selected CAM practices 1 . Definitions which note that CAM satisfies a demand not met by conventional biomedicine usefully explain the complementary function of CAM in society, but still depend unsatisfactorily on the ill-defined shortcomings of biomedicine.…”
Section: Definitions Of Traditional Complementary and Alternative Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Every definition notes that CAM therapies are not part of conventional biomedicine, though the exact phrasing differs and some authors note the intrinsic relativism of any such criterion 1,10 . Indeed, the boundary between conventional medicine and CAM is increasingly muddy as medical schools, general practitioners and hospitals worldwide have introduced CAM therapies alongside mainstream biomedical therapy 16,17,18 , and official regulatory bodies acknowledge and licence selected CAM practices 1 . Definitions which note that CAM satisfies a demand not met by conventional biomedicine usefully explain the complementary function of CAM in society, but still depend unsatisfactorily on the ill-defined shortcomings of biomedicine.…”
Section: Definitions Of Traditional Complementary and Alternative Mmentioning
confidence: 99%
“…Repeatedly, CAM users report that using both forms of care together is more useful than either alone 74,75,76 . However, CAM users do complain about the quality of the doctor-patient relationship during the brief consultations typical of conventional medicine 18,77 . In addition to more satisfying consultations, the philosophies behind CAM have a persuasive appeal which users find compelling 19,78 .…”
Section: The Global Context In Which Tcm Operates and Flourishesmentioning
confidence: 99%
“…Up to 30–40% of children visiting regular paediatric outpatient clinics make use of CAM 1,2 . The types of CAM most frequently used by children are homeopathy, phytotherapy and manual therapies, which are generally offered by CAM practitioners that practise CAM mostly outside the world of mainstream medicine 1,3 . CAM use is often unsupervised since the majority of parents seldom discuss the use of CAM with their general physician or paediatrician 1,4 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 The types of CAM most frequently used by children are homeopathy, phytotherapy and manual therapies, which are generally offered by CAM practitioners that practise CAM mostly outside the world of mainstream medicine. 1,3 CAM use is often unsupervised since the majority of parents seldom discuss the use of CAM with their general physician or paediatrician. 1,4 Last year discussions took place within the Royal Dutch Medical Association (RDMA) about the health risks associated with the limited evidence base of CAM interventions.…”
Section: Introductionmentioning
confidence: 99%
“…those related to emotional problems stand out from the rest. The international literature suggests a high use of these practices for the treatment of mental and emotional problems (Collinge et al, 2005;Weze et al, 2006;Rodrigues-Neto et al, 2008;Russinova et al, 2009;Heiligers et al, 2010) particularly to attend depres-sion and anxiety (Kessler et al, 2001;Gallagher et al, 2001). In Mexico, surveys have reported that a significant percentage of the population with emotional disorders use CAM.…”
Section: Introductionmentioning
confidence: 99%